Correlates of current suicide risk among Thai patients with bipolar I disorder: Findings from the Thai bipolar disorder registry - Sirijit Suttajit (2018)
Background: The Thai Bipolar Disorder Registry was a prospective, multisite, naturalistic study conducted in 24 hospitals across Thailand. This study aimed to examine the correlates of current suicide risk in Thai patients with bipolar I disorder. Methods: Participants were adult inpatients or outpatients with bipolar disorder, based on the Diagnosis and Statistical Manual of Mental Disorders, fourth edition. All were assessed by using the Mini International Neuropsychiatric Interview (MINI), version 5. The severity of current suicide risk was determined by using the total score of the MINI suicidality module. Mood symptoms were assessed by using the Young Mania Rating Scale and the Montgomery Asberg Depression Rating Scale. Results: The data of 383 bipolar I disorder patients were included in the analyses. Of these, 363 (94.8%) were outpatients. The mean (standard deviation) of the MINI suicide risk score was 1.88 (5.0). The demographic/clinical variables significantly associated with the MINI suicide risk scores included age, number of overall previous episodes, the Young Mania Rating Scale score, the Montgomery Asberg Depression Rating Scale scores, and the Clinical Global Impression Severity of Illness Scale for Bipolar Disorder mania score, depression score, and overall score. The variables affecting the differences of suicide risk scores between or among groups were type of first mood episode, a history of rapid cycling, anxiety disorders, and alcohol use disorders. The stepwise multiple linear regression model revealed that the Montgomery Asberg Depression Rating Scale score (β=0.10), a history of rapid cycling (β=6.63), anxiety disorders (β=2.16), and alcohol use disorders (β=2.65) were significantly correlated with the suicide risk score (all P<0.01). Conclusion: A history of rapid cycling, severity of depressive episode, current anxiety disorders, and current alcohol use disorders correlate with current suicide risk among Thai bipolar I disorder patients. Further studies in larger sample sizes are warranted. © 2013 Suttajit et al.